2023
DOI: 10.3389/fpls.2022.1056231
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping for broomrape resistance in sunflower

Abstract: IntroductionSunflower breeding for resistance to the parasitic plant sunflower broomrape (Orobanche cumana Wallr.) requires the identification of novel resistance genes. In this research, we conducted a genome-wide association study (GWAS) to identify QTLs associated with broomrape resistance.MethodsThe marker-trait associations were examined across a germplasm set composed of 104 sunflower accessions. They were genotyped with a 600k AXIOM® genome-wide array and evaluated for resistance to three populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Other studies have identified the position of additional resistance genes, such as Or5 gene conferring resistance to broomrape race E in the upper region of Chr 3 (Tang et al 2003;Pérez-Vich et al 2004). This region was also found to be a hotspot for resistance to more virulent populations (races F and G) in studies using QTL detection (Imerovski et al 2019) and GWAS (Calderón-González et al 2023). Furthermore, Imerovski et al (2019) and Calderón-González et al (2023) identified a second genomic region on Chr 3 associated with broomrape resistance, and Calderón-González et al (2023) found potential genetic associations with broomrape resistance on Chrs 5, 10, 13, and 16.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies have identified the position of additional resistance genes, such as Or5 gene conferring resistance to broomrape race E in the upper region of Chr 3 (Tang et al 2003;Pérez-Vich et al 2004). This region was also found to be a hotspot for resistance to more virulent populations (races F and G) in studies using QTL detection (Imerovski et al 2019) and GWAS (Calderón-González et al 2023). Furthermore, Imerovski et al (2019) and Calderón-González et al (2023) identified a second genomic region on Chr 3 associated with broomrape resistance, and Calderón-González et al (2023) found potential genetic associations with broomrape resistance on Chrs 5, 10, 13, and 16.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, Imerovski et al (2019) and Calderón-González et al (2023) identified a second genomic region on Chr 3 associated with broomrape resistance, and Calderón-González et al (2023) found potential genetic associations with broomrape resistance on Chrs 5, 10, 13, and 16. The biological function of these QTL and/or minor genes remains to be elucidated, although recent studies pointed the possible role in modulating sunflower O. cumana resistance responses of SWEET (Sugars Will Eventually be Exported Transporters) sugar transporter genes (Calderón-González et al 2023), transcription factors of the basic leucine zipper family (Li et al 2023) or genes involved in the biosynthesis of monophenols (4CL2 4-coumarate-CoA ligase (2) or basal defence regulation and salicylic acid signalling activation (EDS1, enhanced disease susceptibility 1) (Huang et al 2022).…”
Section: Introductionmentioning
confidence: 97%
“…The most efficient and economical method for controlling broomrape resistance is crop breeding [ 8 , 9 ]. At present, no broad-spectrum resistant varieties against broomrape have been found, and existing resistant hosts mainly show resistance to specific races; for example, the sunflower P-96 shows dominant resistance to broomrape race E and recessive resistance to the very new race F [ 10 ], and the sunflower HaOr7 mainly controls the Spanish broomrape race F populations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most e cient and economical method of controlling broomrape resistance is crop breeding [8,9] . It is important to clarify the species and genetic diversity of broomrape populations to cultivate varieties that are resistant to broomrape.…”
Section: Introductionmentioning
confidence: 99%